Efficacy of traditional herbs of Bangladeshagainst fish pathogenic fungi - Muniruzzaman, M; Chowdhuri, M B R (Indian Journal of Fisheries, 2011)
Twenty-six species of traditional herbs of Bangladesh were selected to exam-ine their anti-fungal activity against the common fish pathogenic fungi inaquaculture. Extracts of these herbs were applied under in vitro conditionagainst individual fungal pathogen, viz., Achlya sp., Aphanomyces invadansand Saprolegnia sp. Initially a high dose was used to detect the antifungaleffects of the herbs and categorized as high, medium and low effective herbs.Sixteen species of the herbs tested showed anti-fungal effect. Among these, theextracts of C. zedoaria (Bulb), C. longa (Bulb), C. zedoaria (Bulb) plus A. indica(Leaves) and C. longa (Bulb) plus A. indica (Leaves) were high effective againstall of the fungi exposed.Â The minimal inhibitory dose (MID) of the high effec-tive herbs was determined with respect to three fish pathogenic fungi tested.